2022
DOI: 10.1186/s13722-022-00315-4
|View full text |Cite
|
Sign up to set email alerts
|

The Community-Based Medication-First program for opioid use disorder: a hybrid implementation study protocol of a rapid access to buprenorphine program in Washington State

Abstract: Background Opioid use disorder (OUD) is a serious health condition that is effectively treated with buprenorphine. However, only a minority of people with OUD are able to access buprenorphine. Many access points for buprenorphine have high barriers for initiation and retention. Health care and drug treatment systems have not been able to provide services to all—let alone the majority—who need it, and many with OUD report extreme challenges starting and staying on buprenorphine in those care set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Features such as drop-in service availability [ 18 , 23 , 32 ], HIV or other disease screening [ 18 , 20 , 32 , 33 ], syringe exchange [ 18 , 20 , 21 , 27 , 30 , 32 34 ], provision of temporary housing or assistance in securing housing [ 18 , 26 , 30 , 32 , 35 ], case management [ 26 , 30 , 35 ], preventative education [ 18 , 20 ], and the incorporation of an interdisciplinary staff [ 23 , 25 , 26 , 30 , 32 , 35 ] contributed to the effectiveness of community-based programs. For example, the Homelessness Team Program at Cohealth in Melbourne, Australia, offered a fixed site and multiple outreach services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Features such as drop-in service availability [ 18 , 23 , 32 ], HIV or other disease screening [ 18 , 20 , 32 , 33 ], syringe exchange [ 18 , 20 , 21 , 27 , 30 , 32 34 ], provision of temporary housing or assistance in securing housing [ 18 , 26 , 30 , 32 , 35 ], case management [ 26 , 30 , 35 ], preventative education [ 18 , 20 ], and the incorporation of an interdisciplinary staff [ 23 , 25 , 26 , 30 , 32 , 35 ] contributed to the effectiveness of community-based programs. For example, the Homelessness Team Program at Cohealth in Melbourne, Australia, offered a fixed site and multiple outreach services.…”
Section: Resultsmentioning
confidence: 99%
“…Similar services were also offered in IDEA SSP in Miami, Florida [ 33 , 34 ]. Another program focused on drop-in, and easy-access care was the Community-Based Medication-First (CBMF) Program for opioid use disorder (OUD) in Washington State, which provided same-day medication for individuals suffering from OUD [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our data is specific to the state of Missouri, where recent efforts to increase OUD treatment have focused on buprenorphine rather than methadone ( Winograd et al, 2019 ). However, data has shown that “medication-first” initiatives to boost access to OUD have heavily focused on buprenorphine, suggesting that the data from Missouri is likely generalizable to many other regions of the USA ( Banta-Green et al, 2022 ; Brady et al, 2021 ). Finally, while the present study was performed when the DATA 2000 X-waiver was still required, which may limit generalizability, the removal of the X-waiver has not been found to significantly increase buprenorphine prescribing rates,( Luo and Erikson, 2023 ; Stringfellow et al, 2023 ), suggesting that the lessons gained from data preceding X-waiver removal periods will likely still apply to the present.…”
Section: Discussionmentioning
confidence: 99%
“…Critics of buprenorphine PAs point out that many PA requirements are not supported by evidence, including mandatory counseling, dose limits, and predefined tapering schedules . These unnecessarily restrictive requirements run contrary to growing evidence that low-barrier, on-demand addiction care can increase treatment engagement and retention, including in historically marginalized populations …”
Section: Discussionmentioning
confidence: 99%
“…4,23,24 These unnecessarily restrictive requirements run contrary to growing evidence that low-barrier, on-demand addiction care can increase treatment engagement and retention, including in historically marginalized populations. [25][26][27][28] While fairly limited to date, research on the outcomes associated with buprenorphine PAs has been mixed. In the most comprehensive study to date using Medicare claims data, Mark et al 6 found that removal of buprenorphine-naloxone PAs in Medicare Part D plans was associated with an increase of 17.9 prescriptions filled per plan per year, equivalent to approximately a doubling of the number of prescriptions.…”
Section: Discussionmentioning
confidence: 99%